Designing the Human Factors of Professional Ethics in Iran’s Judicial System (Case Study: Justice Departments in the West of the Country) - Yousefi, Yahiya; Nasr Isfahani, Ali; Kazemi, Ali (International Review of Management and Marketing, 2019)
This paper presents human factors related to professional ethics in the judicial system of Iran. This descriptive-survey based research has practical purpose and mix(qualitative-quantitative) based on Grounded Theory, seeking identification and modeling of human factors related to the professional ethics of the judicial system The statistical population used in this paper are the judiciaries in five provinces in the west of Iran. Sampling method in the qualitative section was done theoretically through the snowball method, and quantitative section as scaled random with appropriate allocation of volume based on the structural equations rule, with participation 847 justices and administrative experts. irst step, components related to human factors in qualitative method of coding and interpretive method than the first model designed. In order to test the model, Data using statistical tests such as the Pearson correlation coefficient, regression, factor analysis and exploratory model was fitted through structural equation method to variables. Keywords: Professional ethics, the justice system, Iran. JEL Classifications: D63, J24 DOI: https://doi.org/10.32479/irmm.8169